Countercyclical Macro Prudential Policies in a Supporting Role to Monetary Policy - N'Diaye, Papa. (Washington, D.C. : International Monetary Fund, 2009)
This paper explores how prudential regulations can support monetary policy in reducing output fluctuations while maintaining financial stability. It uses a new framework that blends a standard model for monetary policy analysis with a contingent claims model of financial sector vulnerabilities. The results suggest that binding countercyclical prudential regulations can help reduce output fluctuations and lessen the risk of financial instability. More specifically, countercyclical rules such as countercyclical capital adequacy rules, can allow monetary authorities to achieve the same output and inflation objectives but with smaller adjustments in interest rates. The countercyclical rules can help stem swings in asset prices, lean against a financial accelerator process, and thereby help to lower risks of macroeconomic and financial instability. In economies with fixed exchange rates, where countercyclical monetary policy is not possible, prudential regulations can provide a useful mechanism for mitigating a run-up in asset prices and for promoting output stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet